2020
DOI: 10.29141/2218-5003-2020-11-4-2
|View full text |Cite
|
Sign up to set email alerts
|

The concept of ecosystem in economic and management studies

Abstract: The concept of ecosystem enjoys growing popularity among academics and practitioners around the globe. However, due to the inconsistent use and the vagueness of definitions, the application of the concept in economic and management studies is impeded. The paper systematizes the prerequisites, theoretical foundations and conceptual framework of ecosystems as a concept for describing a new structure of social relations. The methodological basis of the research is organizational ecology theory, dynamic capabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…So Ramenskaya L.A. found that "the number of scientific publications with the keywords "business ecosystem" in google.scholar has grown 6.5 times over the past 18 years" [6]. At the same time, this author, among other representatives of the scientific community, does not fully share the optimism regarding the widespread use of the term ecosystem [7].…”
Section: Resultsmentioning
confidence: 99%
“…So Ramenskaya L.A. found that "the number of scientific publications with the keywords "business ecosystem" in google.scholar has grown 6.5 times over the past 18 years" [6]. At the same time, this author, among other representatives of the scientific community, does not fully share the optimism regarding the widespread use of the term ecosystem [7].…”
Section: Resultsmentioning
confidence: 99%
“…Developing digital environments is a stable trend developed in developing economies (Stonig et al 2022;Rudnik et al 2021). Use of BIM technologies in construction increased urgency of forming the stage-specific digital environments in the course of development project life cycles (Stepanova et al 2019;Bank of Russia 2021;Marnewick and Marnewick 2022;Cabeças and Marques da Silva 2021;Ramenskaya 2020;Riaz et al 2022) with consecutive transformation into the company environment for projects. A digital platform can facilitate interaction between construction industry stakeholders and enable design of an environment (internal and external) for managing investment and construction projects (Hein et al 2020;Yasnitsky et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing the innovation process, ensuring the continuity of the innovation cycle ACHIEVING SUSTAINABILITY OF REGIONAL DEVELOPMENT implemented), the importance of a comprehensive studies of the structure and specificity of the processes of integration and interaction of CIE elements, which, according Y. Su et al, are their most significant characteristics [19]. In fact, understanding the features of the CIE landscape, formed by the level of development of science, technology and business (STB) and their interaction, contributes to the rationalization of the search for ways of innovative growth, making management decisions to create an infrastructure for the development and development of innovations, and intensive development of the network environment.…”
Section: Directions For Implementing Innovations In the Regional Economy Impact Of Global Transformations To Global Dynamics And New Qualmentioning
confidence: 99%
“…It is customary to distinguish the research and commercial components within a certain CIE [19][20][21]. Thus, according D. Oh D. et al, with achievement of a systemic compromise of their goals and interests, it is possible to form effective informational, organizational and economic interactions that contribute to balancing the relationships between the selected subsystems of CIE.…”
Section: Directions For Implementing Innovations In the Regional Economy Impact Of Global Transformations To Global Dynamics And New Qualmentioning
confidence: 99%